Polyphasic evaluation and cytotoxic investigation of isolated cyanobacteria with an emphasis on potent activities of a Scytonema strain - Ngo, Trang T.; Nguyen, Bich-Loan T.; Duong, Tuan A.; Nguyen, Thu-Huyen T.; Nguyen, Thanh L.; Kieu, Kien T.; Do, Minh-Hanh T.; Nguyen, Sang V.; Thang, Nguyen Dinh; Pham, Hang T. L. (Frontiers in Microbiology, 2022)
Cyanobacteria are phototrophic organisms widely found in most types of natural habitats in the tropical regions of the world. In this study, we isolated and identified cyanobacterial strains from paddy soil in Hanoi (Vietnam) and investigated their cytotoxic activities. Five isolated cyanobacterial strains showed distinctive profiles of gene sequences (rRNA 16S and rbcL), phylogenetic placements, and morphological characteristics. Based on the polyphasic evaluation, they were classified as Scytonema bilaspurense NK13, Hapalosiphon welwitschii MD2411, Aulosira sp. XN1103, Desikacharya sp. NS2000, and Desmonostoc sp. NK1813. The cytotoxic screening revealed that extract of strain Scytonema bilaspurense NK13 exhibited potent cytotoxic activities against four human cell lines of HeLa cells, OVCAR-8 cells, HaCaT cells, and HEK-239T cells, with IC50 values of 3.8 µg/mL, 34.2 µg/mL, 21.6 µg/mL and 0.6 µg/mL, respectively. This is the first time a well-classified Scytonema strain from tropical habitat in Southeast Asia has been recognised as a potential producer of cytotoxic compounds.